In Vitro Conservation of Medicinal Plant St. John’s Wort (Hypericum perforatum L.) Through Dilution of Basic Medium - Syahid, Sitti Fatimah (Universitas Perjuangan Tasikmalaya, 2021)
In vitro techniques could be applied for plant conservation through minimal growth. Growth reduction is generally attained by modifying the culture medium and/or the environmental condition. Conservation of St. John’s wort (Hypericum perforatum L.) in vitro through dilution of basic medium was conducted at the Tissue Culture Laboratory of Indonesian Spice and Medicinal Crops Research Institute (ISMCRI) in 2018. Sterile shoots were cultured into Murashige and Skoog (MS) medium by reducing macronutrients. The treatments used were full-MS + 0.1 mg L-1 N6 - benzyladenine (BA) as control; ¾ MS + 0.1 mg L-1 BA; ½ MS + 0.1 mgL-1 BA and ¼ MS + 0.1 mg L-1 BA. Observation of the culture growth was conducted three months after the treatments. The experiment was arranged in Completely Randomized Design with ten replications. The result showed that the use of a dilution of basic medium affected the growth of St. John’s wort. The use of ¼ MS + 0.1 mg L-1 BA composition could suppress culture growth (number of shoots, shoots length and number of leaves), without showing necrotic symptom until three months of conservation. This treatment could be used as an alternative to minimize the culture of St. John’s wort for in vitro conservation.